2007
DOI: 10.1186/1744-8069-3-14
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Mechanism for Neuropathic Pain

Abstract: Among different forms of persistent pain, neuropathic pain presents as a most difficult task for basic researchers and clinicians. Despite recent rapid development of neuroscience and modern techniques related to drug discovery, effective drugs based on clear basic mechanisms are still lacking. Here, I will review the basic neuronal mechanisms that maybe involved in neuropathic pain. I will present the problem of neuropathic pain as a rather difficult task for neuroscientists, and we may have to wait for a lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
104
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(108 citation statements)
references
References 74 publications
2
104
1
1
Order By: Relevance
“…Hippocampus and hippocampus-related limbic structures are proposed to be critical for spatial learning and memory (Kandel, 2001). Unlike the hippocampus, the ACC is critical for affective cognitive functions, including decision making, trace memory, attention, and persistent pain (Zhuo, 2007). ACC LTP can be induced by different induction protocols.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hippocampus and hippocampus-related limbic structures are proposed to be critical for spatial learning and memory (Kandel, 2001). Unlike the hippocampus, the ACC is critical for affective cognitive functions, including decision making, trace memory, attention, and persistent pain (Zhuo, 2007). ACC LTP can be induced by different induction protocols.…”
Section: Discussionmentioning
confidence: 99%
“…First, peripheral injuries trigger plastic changes in the ACC, including an array of activity-dependent immediate early genes, and enhanced synaptic responses (Wei et al, 1999;Wu et al, 2005;Zhuo, 2007). No identification of presynaptic versus postsynaptic mechanisms have been performed in the ACC in case of nerve Figure 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,21 Evidence for the involvement of cortical NR2B receptor in pathological pain comes first from the so-called Doogie smart mice. 69 In this transgenic mouse with selective forebrain NMDA NR2B overexpression, electrophysiological and behavioral studies found that the NR2B transgenic mice are superior performers in memory tests, with significant enhanced hippocampal CA1 LTP.…”
Section: Function In Chronic Painmentioning
confidence: 99%
“…Understanding neuropathic pain therefore requires understanding of plastic changes in somatosensory pathways, and targeting central plasticity is becoming a major direction for identifying pain-relieving medications. 1,2 Signaling molecules that are involved in injury-related plasticity may provide potential drug targets for treating neuropathic pain. Among several candidates, the NMDA receptor, one of the major glutamate receptors that is important for synaptic plasticity, has been intensively investigated by both academic and pharmaceutical companies.…”
Section: Introductionmentioning
confidence: 99%